PENGARUH PENILAIAN PEMBIAYAAN TERHADAP KEPUTUSAN PEMBERIAN PEMBIAYAAN KREDIT MOBIL PADA PT. TRIHAMAS FINANCE CABANG MADIUN - Purwanto .; Apriyanti . (CAPITAL: Jurnal Ekonomi dan Manajemen, 2017)
This study aimed to obtain findings about the influence eksplanitif tested financing vote against the decision to grant credit. This study uses a quantitative research design causal. The subjects were Pt. TrihamasMadiun branch and its object is the credit assessment and lending decisions are collected using a questionnaire and analyzed using multiple linear regression analysis. The results showed that the assessment of financing postitif 5C and significant influence lending decisions.  Keywords: Assessment of financing, lending decisions.